2020
DOI: 10.3389/fmed.2020.00206
|View full text |Cite
|
Sign up to set email alerts
|

Differential Methylation in Promoter Regions of the Genes NR3C1 and HSP90AA1, Involved in the Regulation, and Bioavailability of Cortisol in Leukocytes of Women With Preeclampsia

Abstract: Introduction: Hypertensive disorders are of interest in obstetrics and gynecology because they are the second place among causes of maternal mortality and a source of complications in the short, mid, and long term. Even if the pathophysiological process behind preeclampsia (PE) is still unknown, stress factors have been revealed to play an important role in the genesis of this pathologic process. Methods: A case-control study was designed with the purpose of determining if there is a differential methylation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…And we also identified that the acetylation level of K209 on HSP90AA1 was increased in the GDM placentas. In addition, one study of DNA methylation found differential methylation of HSP90AA1 may have a regulatory role in response to stress for women with PE [34]. We identified that the acetylation level of K292 on HSP90AA1 was increased in PE placental tissues.…”
Section: Discussionmentioning
confidence: 76%
“…And we also identified that the acetylation level of K209 on HSP90AA1 was increased in the GDM placentas. In addition, one study of DNA methylation found differential methylation of HSP90AA1 may have a regulatory role in response to stress for women with PE [34]. We identified that the acetylation level of K292 on HSP90AA1 was increased in PE placental tissues.…”
Section: Discussionmentioning
confidence: 76%
“…CEBPB (CCAAT enhancer binding protein beta) [38], ACSL4 [39], MBD2 [40], ULK1 [41], NUCB2 [42], TWIST1 [43], HOOK2 [44], CLDN7 [45], TBK1 [46], YIPF6 [47], TFRC (transferrin receptor) [48], ENPP2 [49], SLIT2 [50], MFGE8 [51], FAT1 [52], GPC4 [53], COL6A3 [54], EGFL6 [55], AOC3 [56], CCN2 [57], LYVE1 [58], RARA (retinoic acid receptor alpha) [59], COL18A1 [60], THY1 [61], CD36 [62], PEMT (phosphatidylethanolamine N-methyltransferase) [63], AIF1L [64], OXTR (oxytocin receptor) [65], LMNA (lamin A/C) [66], CXCL14 [67], DKK3 [68], ANGPTL2 [69] and CMTM7 [70] were reported to be associated with obesity, but these genes might be linked with progression of GDM. AHR (aryl hydrocarbon receptor) [71], STS (steroid sulfatase) [72], PLAC1 [73], CYP11A1 [74], PSG11 [75], STAT5B [76], TLR3 [77], FOLR1 [78], HSPB1 [79], HSP90AA1 [80], ANXA4 [81], ATF3 [82], DAPK1 [83], ENTPD1 [84], ABL1 [85], VSIG4 [86], CD99 [87], VWF (von Willebrand factor) [88], PODXL (podocalyxin like) [89], PDPN (podoplanin) [90], RND3 [91], VCAN (versican) [92], AXL (AXL receptor tyrosine kinase) [93], PIEZO1 [94], GAS6 [93], LAMA4 [95], CAV1 [96], DLL1 [97], CD44 [98], CD81 [99], SMAD3 [100], NES (nestin) [101], DCN (decorin) [102], AGTR1 [103], SLIT3 [104], B2M [105], STAT3 [106], STC1 [107] and ADAMTS1 [108] were shown to participate in facilitating the preeclampsia. Majchrzak-Celiń ka et al [109] ...…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has examined stress during pregnancy and methylation of glucocorticoid pathway and stress genes, though most of these studies have conducted DNAm analyses in the immediate postpartum period [16][17][18][19][20][21]. In a sample of pregnant women (N = 83) from Belgium, psychosocial stress and cortisol was measured at each trimester, and pregnancy-related anxiety was found to be associated with NR3C1 methylation in cord blood [16].…”
Section: Introductionmentioning
confidence: 99%
“…In a sample of pregnant women (N = 83) from Belgium, psychosocial stress and cortisol was measured at each trimester, and pregnancy-related anxiety was found to be associated with NR3C1 methylation in cord blood [16]. A case-control study of postpartum Mexican women (N = 40) compared women with preeclampsia and normotensive women and found differential methylation patterns in promotor regions of genes, including NR3C1 among women with preeclampsia, suggesting a regulatory role in response to stress in pregnancy [18]. Another study examined chronic and war-related stress among pregnant women (n = 24) from the Democratic Republic of Congo and methylation of HPA genes at birth.…”
Section: Introductionmentioning
confidence: 99%